MANAGING FINANCE INVESTMENT: FACTORS OF INVESTMENT APPEAL - Elena V. Semenkova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article discusses conditions of finance investment in the development of productive forces in Russia. Factors of investment appeal to global investors are shown. The author analyzes key factors determining investment appeal of finance investment in tools of Russian stock market: dynamics of macro-economic indicators, dividend profitability, corporate governance, infrastructure of finance market. Interconnection between liquidity and volatility of Russian stock market and the nature of transactions - speculative and investment - was researched. Risks of managing finance investment based on tools and mechanisms of stock market were estimated. The author worked out recommendations aimed at attracting investment capital on the basis of instruments and tools of stock market and designed steps necessary to intensify factors of investment appeal of Russian stock market.